Mitochondrial dysfunction in hypertension: mechanistic pathways and therapeutic implications - Jiao Tian; Lin Yi; Yuyuan Lu; Yushun Kou; Lingna Zhang; Penghui Jin; Xiaoke Wang; Tao Wu; Xin Yang; Yiyuan Wang; Ruiling Ma (Functional & Integrative Genomics, 2026)

DlERF98 transcription factor mediates salicylic acid-induced disease resistance in postharvest longans by activating phenylpropanoid metabolism - Qi Chen; Zhongqi Fan; Ruiling Zhuo; Yifen Lin; Hui Wang; Boqiang Li; Shiping Tian; Mengshi Lin; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2026)

Selective iron removal from Fe-PGMs alloys for platinum group metals concentration: Dissolution behavior of PGMs and ultrasound-assisted leaching - Han Yang; Yong Li; Xilong Wu; Ruiling Yuan; Chao Wang; Shengnan Lin; Jibiao Han; Kuo Liu (Journal of Environmental Chemical Engineering, 2026)

1-Methylcyclopropene-mediated organic acid and sugar homeostasis enhances postharvest quality and shelf-life of fresh goji berry - Maratab Ali; Huizhi Chen; Weijie Wu; Ben Niu; Xiangjun Fang; Chaoyi Shen; Guannan Wang; Hangjun Chen; Ting Huang; Ming Yin; Ruiling Liu; Haiyan Gao (Food Chemistry, 2026)

A 3D correlation spectroscopy framework for spectral feature decoupling: Enabling precise authentication and quantification of dairy cream fat adulteration - Xijun Wu; Xuan Zheng; Shixin Wang; Congyu Lei; Heying Zhang; Tianhao Du; Ruiling Tian (Analytica Chimica Acta, 2026)

Modulation of hyporheic exchange and solute transport by plant cluster configurations - Siyi Zhang; Yihang Yang; Yuhang Tian; Ruiling Long; Kaiwen Zhang; Guangqiu Jin; Xinyi Luo; Guiqiao Wang (Advances in Water Resources, 2026)

Comparative effects of liquid nitrogen rapid freezing, micro-freezing liquid-assisted freezing, and conventional freezing on the physicochemical properties, moisture distribution, microstructure, and protein characteristics of beef steaks - Ling Jiang; Donghong Liu; Wenjun Wang; Ruiling Lv; Songfeng Yu; Yunli Deng; Jianwei Zhou (Food Control, 2026)

A dual-dynamic-bond network enabled, ultra-stretchable, and self-healing hydrogel for fresh produce damage prevention in postharvest logistics - Guannan Wang; Mengqi Zheng; Huizhi Chen; Ruiling Liu; Weijie Wu; Xiangjun Fang; Chaoyi Shen; Hangjun Chen; Haiyan Gao (Chemical Engineering Journal, 2026)

Explainable machine learning for coagulant dosage prediction in coal port wastewater treatment - Haotian Xue; Hanrui Zhang; Mingyu Zhang; Hao Wang; Ruiling Zhang; Qian Cheng; Jingyi Zhao; Bo Wang; Liming Yuan; Shanshan Yuan; Zhenyu Song (Marine Pollution Bulletin, 2026)

Occurrence, fate, and ecological risk of rubber-derived chemicals in a municipal wastewater treatment plant: Insights from unit-scale removal analysis - Qian Wang; Ruiling Zhang; Yueyan Wen; Zixi Huang; Chang-Er Chen; Pengran Guo (Process Safety and Environmental Protection, 2026)

A resilience-based approach to safety barrier performance assessment of blended hydrogen natural gas pipeline system - Ruiling Li; Guojin Qin; Guoqing Xiao; Yihuan Wang (Process Safety and Environmental Protection, 2026)

DCC and ADP modulate the disease progression in postharvest longan caused by Phomopsis longanae Chi in relation to ROS metabolism and cell wall integrity - Xiang Gao; Xiaoxuan Wang; Wenjing Lin; Huili Zhang; Ruiling Zhuo; Yihui Chen; Boqiang Li; Shiping Tian; Hetong Lin; Yifen Lin (Postharvest Biology and Technology, 2026)

Effect of liquid-medium properties on ultrasound inactivation efficiency and mechanism against Escherichia coli and Listeria monocytogenes - Bin Yang; Tingting Chen; Ruyu Zhang; Haiqi Chen; Wenjun Wang; Ruiling Lv; Donghong Liu (Food Bioscience, 2026)

A Comparative Study on the Efficiency Process of Cellulosic Wastewater Fermentation by Oleaginous Yeasts - Shimiao Yao; Hailong Li; Ruiling Gao; Xuefang Chen; Can Wang; Lian Xiong; Xinde Chen (Indian Journal of Microbiology, 2026)

Biochar enhances rice rhizodeposited carbon stabilization through distinct pathways of iron association and aggregate occlusion in two contrasting paddy soils - Ruiling Ma; Yujia Yu; Ruiyu Wang; Zheng Zhao; Zuhang Shen; Qi Yi; Shaopan Xia; Rongjun Bian; Xuhui Zhang; Zhiwei Liu; Kun Cheng; Jufeng Zheng (Biology and Fertility of Soils, 2026)

Unraveling the spatial chemical heterogeneity of Lentinula edodes: Integrative metabolomics and machine learning for cultivar and origin classification - Shenglong Lu; Chaoyi Shen; Ben Niu; Ruiling Liu; Huizhi Chen; Hangjun Chen; Xiangjun Fang; Lishu Wang; Ming Yin; Weijie Wu; Haiyan Gao (Food Chemistry, 2026)

DlNAC41 and DlNAC100 transcription factors modulate longan pulp breakdown via adjusting the expression of cell wall degradation-related genes - Hui Wang; Wenlong Zhou; Xinyue Mu; Zhongqi Fan; Ruiling Zhuo; Yihui Chen; Wangjin Lu; Boqiang Li; Shiping Tian; Yifen Lin; Hetong Lin (Postharvest Biology and Technology, 2026)

DlbHLH66 transcription factor is involved in the acidity differences in the pulp of fresh longan cv. ‘Fuyan’ and ‘Dongbi’ during storage - Zhongqi Fan; Lingzhen Zeng; Shucheng Li; Hui Wang; Ruiling Zhuo; Yifen Lin; Yihui Chen; Wangjin Lu; Boqiang Li; Shiping Tian; Hetong Lin (Postharvest Biology and Technology, 2026)

Separation and enrichment of platinum from spent petroleum reforming catalysts via carrier-directed dissolution under alkaline conditions - Qingfeng Xiong; Han Yang; Lang Liu; Jibiao Han; Yu Shen; Wenhui Ma; Yakun Zhang; Ruiling Yuan; Chao Wang (Journal of Environmental Chemical Engineering, 2026)

Sustainable corecovery of lithium, rubidium, and cesium from lepidolite via calcium chloride–sodium lignosulfonate roasting integrated with precipitation–solvent extraction - Guangyu Duan; Ruiling Du; Guangqian Li; Xin Ma; Zhanfang Cao; Hong Zhong; Shuai Wang (Chemical Engineering Journal, 2026)

The changes of antioxidant system, membrane integrity and phenolics metabolism participate in bongkrekic acid and adenosine triphosphate-mediated energy status regulating longan pericarp browning - Meiling Li; Hetong Lin; Ruiling Zhuo; Boqiang Li; Yifen Lin; Yihui Chen; Zhongqi Fan; Hui Wang (Postharvest Biology and Technology, 2026)

Surface-active ionic liquid/SDS-based supramolecular solvent microextraction for separation and enrichment of sulfonylurea hypoglycemic drugs prohibited in health food - Xingzhe Shao; Ruiling Wu; Jinyu Zhou; Jun Zhang; Jinghui Wang; Songbo Jiao; Yating Zhang; Zhibing Wang; Zhen Wang; Fengqing Zhang (Food Chemistry, 2026)

EBV-miR-BART14-3p Targets LACTB to Enhance Gastric Cancer Cell Proliferation and Migration - Xiaomin Huang; Xuhui Zhao; Yujiao Qi; Tian Lan; Ruiling Wang; Shuang Liang; Yuxiu Ma; Cuixia Di; Hongling Li (Biochemical Genetics, 2026)

State-of-the-art insights into hydrogel innovations from structural engineering to smart preservation: Research trends and future directions - Yan Xu; Yiyi Cheng; Tao Yang; Huizhi Chen; Ben Niu; Xiangjun Fang; Weijie Wu; Chaoyi Shen; Guannan Wang; Bangdi Liu; Ruiling Liu; Haiyan Gao (Trends in Food Science & Technology, 2026)

Dynamic changes in epidermal wax composition and quality of three goji berry varieties during postharvest storage - Ben Niu; Zihao Zong; Yifan Ding; Huizhi Chen; Weijie Wu; Maratab Ali; Mohamed A. Farag; Xiangjun Fang; Ting Huang; Chaoyi Shen; Li-shu Wang; Ruiling Liu; et al. (Postharvest Biology and Technology, 2026)

Revealing the influencing pathways and mechanisms of inorganic salts on the catalytic ozonation of petrochemical wastewater - Zhikai Qin; Fang Wang; Yue Yuan; Guoxin Ma; Yin Yu; Yutong Duan; Ruiling Bao; Changyong Wu (ENGINEERING Environment, 2026)

Efficacy and antibacterial mechanism of intense pulsed light against Escherichia coli: Photochemical and physical effect - Zihan Ye; Tingting Chen; Ruyu Zhang; Ruiling Lv; Songfeng Yu; Jianwei Zhou; Wenjun Wang; Donghong Liu (Food Bioscience, 2025)

Exploring the potential of ultrasound to improve the physicochemical properties of protein-based emulsion gels: by ultrasonically treating emulsion (pre-emulsification, post-emulsification) and substrate solution respectively - Ruiling Li; Chao Ma; Ningzhe Wang; Jing Wang; Xin Yang (Food Hydrocolloids, 2025)

Hypothermal effects of cold anesthesia on the vitality and muscle quality of live Chinese mitten crab (Eriocheir sinensis) - Laixin Chen; Yanchao Han; Honglei Mu; Ben Niu; Ruiling Liu; Guannan Wang; Huizhi Chen; Lishu Wang; Hangjun Chen; Haiyan Gao (Food Research International, 2025)

Ultrasound-enhanced inactivation of Escherichia coli O157: H7 from wastewater in the citric acid-assisted nano zerovalent iron heterogeneous Fenton system: Effectiveness and mechanisms - Ting-Ting Chen; Wenjun Wang; Ruiling Lv; Donghong Liu (Journal of Water Process Engineering, 2025)

Comparative transcriptomic and metabolomic analyses reveal the role of acidic electrolyzed-oxidizing water in enhancing disease resistance in Phomopsis longanae Chi-infected longans - Meiling Li; Zhongqi Fan; Xiaoze Dai; Mengshi Lin; Yifen Lin; Hui Wang; Ruiling Zhuo; Yen-Con Hung; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2025)

Salicylic acid nanoliposomes treatment alleviates chilling injury in postharvest baby ginger by regulating membrane lipid metabolism - Zhenzhen Mi; Honglei Mu; Yanchao Han; Ruiling Liu; Ben Niu; Guannan Wang; Huizhi Chen; Haiyan Gao; Hangjun Chen (Food Chemistry, 2025)

Silk protein functionalized coatings and films as a novel biomaterial for fruit and vegetable preservation: current state and future prospects - Yan Wang; Weijie Wu; Ruiling Liu; Huizhi Chen; Haiyan Gao (Current Opinion in Food Science, 2025)

The transcription factor CeWRI3 functions in TAG accumulation through activating CeOLE2 in Cyperus esculentus - Zhi Zou; Xiaowen Fu; Na Li; Panyan Zheng; Ruiling Wang; Hongyan Liu; Jiaquan Huang; Yongguo Zhao (Plant Cell Reports, 2025)

Effect and mechanism of ultrasound time and storage time on physicochemical properties, 3D printing accuracy, and microstructure of ovalbumin–gellan gum emulsion gels - Ruiling Li; Ningzhe Wang; Chao Ma; Jiacheng Wang; Jing Wang; Xin Yang (Food Chemistry, 2025)

Development of cushioning-antibacterial dual-functional cellulose packaging and its application for the Chinese bayberry during simulated transportation vibration - Yifan Xue; Ben Niu; Yanchao Han; Weijie Wu; Guannan Wang; Ming Yin; Xiangjun Fang; Ruiling Liu; Hangjun Chen; Haiyan Gao; Honglei Mu (Food Packaging and Shelf Life, 2025)

Fe-loaded hollow fiber carbon microfiltration membrane and its BPA removal performance based on electro-Fenton - Ruiling Luo; Zhongcheng Yang; Yucheng Wang; Yue Yang; Lanyue Qi; Junwen Qi; Zhigao Zhu; Yujun Zhou; Jiansheng Li (Journal of Environmental Chemical Engineering, 2025)

Advancements and perspectives of antimicrobial effects of combination mode nonthermal strategies - A review - Ruyu Zhang; Yong Deng; Ruiling Lv; Wenjun Wang; Donghong Liu (Food Bioscience, 2025)

Advancements and perspectives of novel freezing and thawing technologies effects on meat: A review - Ling Jiang; Donghong Liu; Wenjun Wang; Ruiling Lv; Songfeng Yu; Jianwei Zhou (Food Research International, 2025)

Construction and formation mechanism of phase-change polysaccharide–protein composite emulsion gels: For simultaneous printing of food products with complex structures and fine patterns - Ruiling Li; Ningzhe Wang; Chao Ma; Jiacheng Wang; Jing Wang; Xin Yang (Food Hydrocolloids, 2025)

Silk protein: A novel antifungal and edible coating for strawberry preservation - Yan Wang; Weijie Wu; Ruiling Liu; Ben Niu; Xiangjun Fang; Hangjun Chen; Mohamed A. Farag; Li-Shu Wang; Guannan Wang; Hailong Yang; Huizhi Chen; Haiyan Gao (Food Chemistry, 2025)

High UV-shielding polyvinyl alcohol/chitosan-based transparent bioplastic film for food preservation - Mei Bao; Honglei Mu; Ben Niu; Ruiling Liu; Huizhi Chen; Hangjun Chen; Lishu Wang; Yanchao Han; Guannan Wang; Haiyan Gao (Food Packaging and Shelf Life, 2025)

Mechanical behavior and compositional variation of weathered granite soil with different degrees of weathering - Yi Shan; Kezheng Yang; Ruiling Jia; Yadong Li; Yizhao Wang; Jie Cui (Bulletin of Engineering Geology and the Environment, 2025)

Characterization of the Bacillus cereus spore killed by plasma-activated water (PAW) - Xiao Hu; Pengfei Ge; Xiaomeng Wang; Xinyu Liao; Jinsong Feng; Ruiling Lv; Tian Ding (Food Research International, 2024)

Half-antibody spur one-to-one recognition mechanism can function with chemical-staining technology for next-generation lateral flow immunoassay - Jingke Xu; Jing Zhou; Kai Liu; Tong Bu; Leina Dou; Rui Shu; Sijie Liu; Shaochi Wang; Xuechi Yin; Daohong Zhang; Ruiling Zhang; Jie Cheng; et al. (Chemical Engineering Journal, 2024)

Exogenous microbubbles contribute to valorization of microalgal compounds by ultrasound-assisted extraction - Yong Deng; Lihua Fan; Wenjun Wang; Ruiling Lv; Donghong Liu (Bioresource Technology, 2024)

Atmospheric reactive nitrogen conversion kicks off the co-directional and contra-directional effects on PM2.5-O3 pollution - Feng Wang; Chun Zhang; Yi Ge; Ruiling Zhang; Bijie Huang; Guoliang Shi; Xiaoli Wang; Yinchang Feng (Journal of Hazardous Materials, 2024)

Identification of extracted antioxidants from Citrus aurantium 'Changshanhuyou' residue against digestive enzyme activities and airway smooth muscle cells proliferation using UPLC-MS/MS - Xinyue Zhou; Junyang Wang; Han Wang; Peng Lu; Qiong Huang; Ming Huang; Ruiling Lv; Donghong Liu; Wenjun Wang (Food Bioscience, 2024)

Novel overlapping constructed wetlands with water drops reoxygenation and lightweight fillers for decentralized wastewater treatment - Zhao Shuyuan; Li Guo; Shui Paipai; Nie Wenbo; Qu Han; Yan Jun; Li Hong; Wang Ruiling (Bioresource Technology, 2024)

Wolbachia titers are relate to sex determination of Trichogramma pretiosum - Zhuangting Xiao; Xin Xu; Qiling Liang; Congying Zhu; Xinyu He; Ruiling Hu; Yurong He; Desen Wang (Journal of Pest Science, 2024)

Amino-functionalized graphene oxide affects bacteria–phage interactions in aquatic environments - Ying Li; Kexin Zhang; Yansong Yin; Xinxin Kong; Ruiling Zhang; Haijun Wang; Zhong Zhang (Water Research, 2024)

Simulated gastrointestinal digestion of walnut protein yields anti-inflammatory peptides - Wei Xia; Yuan Gao; Xiangjun Fang; Long Jin; Ruiling Liu; Li-Shu Wang; Yangyong Deng; Junlong Gao; Hailong Yang; Weijie Wu; Haiyan Gao (Food Chemistry, 2024)

Drought shortens subtropical understory growing season by advancing leaf senescence - Huanfa Sun; Liming Yan; Zhao Li; Wanying Cheng; Ruiling Lu; Xingli Xia; Jiaye Ping; Chenyu Bian; Ning Wei; Cuihai You; Songbo Tang; Ying Du; et al. (Global Change Biology, 2024)
Subtropical forests, recognized for their intricate vertical canopy stratification, exhibit high resistance to extreme drought. However, the response of leaf phenology to drought in the species‐rich understory remains poorly understood. In this study, we constructed a digital camera system, amassing over 360,000 images through a 70% throughfall exclusion experiment, to explore the drought response of understory leaf phenology. The results revealed a significant advancement in understory leaf senescence phenology under drought, with 11.75 and 15.76 days for the start and end of the leaf‐falling event, respectively. Pre‐season temperature primarily regulated leaf development phenology, whereas soil water dominated the variability in leaf senescence phenology. Under drought conditions, temperature sensitivities for the end of leaf emergence decreased from −13.72 to −11.06 days °C −1 , with insignificance observed for the start of leaf emergence. Consequently, drought treatment shortened both the length of the growing season (15.69 days) and the peak growth season (9.80 days) for understory plants. Moreover, this study identified diverse responses among intraspecies and interspecies to drought, particularly during the leaf development phase. These findings underscore the pivotal role of water availability in shaping understory phenology patterns, especially in subtropical forests.

Failure probability estimation of natural gas pipelines due to hydrogen embrittlement using an improved fuzzy fault tree approach - Guojin Qin; Ruiling Li; Ming Yang; Bohong Wang; Pingan Ni; Yihuan Wang (Journal of Cleaner Production, 2024)

Evaluation of multiscale mechanisms of ultrasound-assisted extraction from porous plant materials: Experiment and modeling on this intensified process - Jiaheng Li; Wenjun Wang; Weidong Xu; Yong Deng; Ruiling Lv; Jianwei Zhou; Donghong Liu (Food Research International, 2024)

Biomimetic hybrid porous microspheres with plant membrane-wall structure for evaluating multiscale mechanisms of ultrasound-assisted mass transfer - Jiaheng Li; Wenjun Wang; Weidong Xu; Songfeng Yu; Ruiling Lv; Jianwei Zhou; Donghong Liu (Chemical Engineering Journal, 2024)

4D food printing: Key factors and optimization strategies - Ningzhe Wang; Ruiling Li; Xibo Wang; Xin Yang (Trends in Food Science & Technology, 2024)

Nanoparticle encapsulation using self-assembly abietic acid to improve oral bioavailability of curcumin - Ying Han; Hua Zhang; Haitian Zhao; Shiyao Fu; Ruiling Li; Zhili Wang; Yangxin Wang; Weihong Lu; Xin Yang (Food Chemistry, 2024)

Changes of water in different states during peat soil compression - Bo Peng; Ruiling Feng; Lijian Wu; Pengcheng Wang; Yupeng Shen (Bulletin of Engineering Geology and the Environment, 2024)

Importance sampling-based probabilistic performance modeling of low-, mid- and high-strength pipelines under coupling effect of hydrogen-induced damage and corrosion - Yihuan Wang; Zhenwei Zhang; Siming Liu; Ailin Xia; Ruiling Li; Guojin Qin (Process Safety and Environmental Protection, 2023)

Development of bio-based PLA/cellulose antibacterial packaging and its application for the storage of shiitake mushroom - Weitao Wang; Ben Niu; Ruiling Liu; Hangjun Chen; Xiangjun Fang; Weijie Wu; Guannan Wang; Haiyan Gao; Honglei Mu (Food Chemistry, 2023)

Enhanced viability of probiotics in composite hydrogel beads - Fan Zhang; Ruiling Wang; Lichen Zhang; Lei Yan; Yuze Jia; Jie Yang; Xin Wang; Xin Lü (Journal of Food Engineering, 2023)

Preparation of heterojunction C3N4/WO3 photocatalyst for degradation of microplastics in water - Xiang Wang; Zhihao Zhu; Jinwei Jiang; Ruiling Li; Junjie Xiong (Chemosphere, 2023)

Facile surface pseudohalide pretreatment of quantum dots for efficient photovoltaics - Zhe Sun; Qinggang Hou; Ruiling Zhang; Jiaxuan Cheng; Jiahua Kong; Keke Wang; Feng Liu; Zhonglin Du; Jianguo Tang (Chemical Engineering Journal, 2023)

H2O2 and Ca2+ are involved in the embryogenic potential loss of cells during long-term proliferation culture in Pinus massoniana - Yin Wang; Ruiling Yao (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

A galacturonic acid-rich polysaccharide from Diospyros kaki peel: Isolation, characterization, rheological properties and antioxidant activities in vitro - Yanlong Cui; Ruiling Wang; Siyue Cao; Mohamedelfatieh Ismael; Xin Wang; Xin Lü (Food Chemistry, 2023)

Molecular mechanism of metamorphic alteration on traces of early life in banded iron formations - Jingbo Nan; Zidong Peng; Chao Wang; Dominic Papineau; Zhenbing She; Zixiao Guo; Xiaotong Peng; Junlie Zhou; Yingjie Hu; Weiqi Yao; Ruiling Zhang; Changle Wang; et al. (Earth and Planetary Science Letters, 2023)

Cation engineering in low-dimensional organic-inorganic copper halides for high color rendering index WLEDs - Hong Yin; Wenzhi Li; Zhongyi Wang; Pengyuan Wang; Xin Xu; Peigeng Han; Xin Mao; Feng Liu; Keli Han; Junsheng Chen; Ruiling Zhang (Chemical Engineering Journal, 2023)

Graphene oxide affects bacteriophage infection of bacteria by promoting the formation of biofilms - Xinyu Zhang; Ying Li; Kexin Zhang; Yansong Yin; Jie Wang; Luocheng Wang; Zhexing Wang; Ruiling Zhang; Haijun Wang; Zhong Zhang (Science of The Total Environment, 2023)

Clogging mechanisms of biological aerobic filter in a petro-chemical wastewater treatment plant: A field study - Xinning Gao; Lixin Zhao; Ruiling Zhang; Shuo Wang; Yanli Pan; Songyan Qin (Journal of Water Process Engineering, 2023)

Applications, impacts, and management of biochar persistent free radicals: A review - Ruirui Zhang; Ruiling Zhang; Andrew R. Zimmerman; Hailong Wang; Bin Gao (Environmental Pollution, 2023)

Characterization of Short-chain fatty acid-producing and cholesterol assimilation potential probiotic Lactic acid bacteria from Chinese fermented rice - Nageena Qayyum; Wang Shuxuan; Qin Yantin; Wang Ruiling; Shuang Wang; Mohamedelfatieh Ismael; Xin Lü (Food Bioscience, 2023)

Extensive regulation of pH-responsive transcription factor PacC on secondary metabolism contributes to development and virulence of Botrytis cinerea - Ruiling Zhuo; Guangjin Li; Huaimin Peng; Yuanyuan Zong; Xiao Wang; Shasha Lu; Yong Chen; Zhanquan Zhang; Shiping Tian; Boqiang Li (Postharvest Biology and Technology, 2023)

An integrated modeling method of uncertainties: application-orientated fuzzy random spatiotemporal analysis of pipeline structures - Yihuan Wang; Ruiling Li; Ailin Xia; Pingan Ni; Guojin Qin (Tunnelling and Underground Space Technology, 2023)

Fe-ZIF-derived hollow porous carbon nanofibers for electromagnetic wave absorption - Ruiling Sun; Guilong Yan; Xunlong Zhang; Zhenyu Li; Jingyu Chen; Li Wang; Yuanpeng Wu; Yiqun Wang; Han Li (Chemical Engineering Journal, 2023)

Assessing the mechanism for flood control: a case of plain river network cities under extreme rainfalls - Yihu Wang; Cheng Gao; Jin Xu; Wei Zhang; Liangliang She; Qianqian Zhang; Ruiling Bao (Environmental Science and Pollution Research, 2022)

Complete genome sequence of Edgeworthia chrysantha mosaic-associated virus, a tentative new member of the genus Coguvirus (family Phenuiviridae) - Xiaoru Wang; Ruiling Liao; Xinying Yang; Qiyan Liu; Song Zhang; Mengji Cao (Archives of Virology, 2022)

Treatment of Wastewater-CPL by Biochar-Based Fenton-Like Catalyst in the Presence of Micro-nano Bubbles - Ruiling Zhang; Jiajun Wang; Jianyu Yang; Songyan Qin; Feiyue Li; Lixin Zhao; Zhe Zhu (Water, Air, & Soil Pollution, 2022)

Efficacy and safety of aripiprazole once-monthly versus oral aripiprazole in Chinese patients with acute schizophrenia: a multicenter, randomized, double-blind, non-inferiority study - Le Xiao; Qian Zhao; An-ning Li; Jushui Sun; Bin Wu; Lina Wang; Honggeng Zhang; Ruiling Zhang; Keqing Li; Xiaojin Xu; Tiebang Liu; Wenshun Zhang; et al. (Psychopharmacology, 2022)

Biochar Derived from Treated Lotus Stem and Adsorption of Phthalic Acid Esters - Ruiling Zhang; Linlin Chen; Binbin Qiu; Xiaojing Sun; Songyan Qin; Bo Wang; Feiyue Li; Lixin Zhao; Zhe Zhu (Water, Air, & Soil Pollution, 2021)

Increased endogenous gibberellin level inhibits root growth of Pinus massoniana Lamb. plantlets during long-term subculture - Yin Wang; Ruiling Yao (In Vitro Cellular & Developmental Biology - Plant, 2020)

Correlation between the epigenetic modification of histone H3K9 acetylation of NR2B gene promoter in rat hippocampus and ethanol withdrawal syndrome - Duan Li; Yanqing Zhang; Yanting Zhang; Qi Wang; Qin Miao; Yahui Xu; Jair C. Soares; Xiangyang Zhang; Ruiling Zhang (Molecular Biology Reports, 2019)

Correction to: Identification of β‑carboline and canthinone alkaloids as anti‑inflammatory agents but with different inhibitory profile on the expression of iNOS and COX‑2 in lipopolysaccharide‑activated RAW 264.7 macrophages - Pan Liu; Huixiang Li; Ruiling Luan; Guiyan Huang; Yanan Liu; Mengdi Wang; Qiuli Chao; Liying Wang; Danna Li; Huaying Fan; Daquan Chen; Linyu Li; et al. (Journal of Natural Medicines, 2019)

Identification of β-carboline and canthinone alkaloids as anti-inflammatory agents but with different inhibitory profile on the expression of iNOS and COX-2 in lipopolysaccharide-activated RAW 264.7 macrophages - Pan Liu; Huixiang Li; Ruiling Luan; Guiyan Huang; Yanan Liu; Mengdi Wang; Qiuli Chao; Liying Wang; Danna Li; Huaying Fan; Daquan Chen; Linyu Li; et al. (Journal of Natural Medicines, 2019)

De novo RNA-seq and functional annotation of Ornithonyssus bacoti - DongLing Niu; RuiLing Wang; YaE Zhao; Rui Yang; Li Hu (Experimental and Applied Acarology, 2018)

Diversity of tick species on domestic animals in Shandong Province, China, using DNA barcoding - Ruiling Zhang; Aihua Zhao; Xuejun Wang; Zhong Zhang (Experimental and Applied Acarology, 2017)

Occurrence, Distribution and Ecological Risks of Fluoroquinolone Antibiotics in the Dongjiang River and the Beijiang River, Pearl River Delta, South China - Ruiling Zhang; Ruijie Zhang; Shichun Zou; Ying Yang; Jun Li; Yinghui Wang; Kefu Yu; Gan Zhang (Bulletin of Environmental Contamination and Toxicology, 2017)

Occurrence and distribution of antibiotics in multiple environmental media of the East River (Dongjiang) catchment, South China - Ruijie Zhang; Ruiling Zhang; Jun Li; Zhineng Cheng; Chunling Luo; Yinghui Wang; Kefu Yu; Gan Zhang (Environmental Science and Pollution Research, 2017)

cDNA library construction of two human Demodexspecies - DongLing Niu; RuiLing Wang; YaE Zhao; Rui Yang; Li Hu; YuYang Lei; WeiChao Dan (Acta Parasitologica, 2017)
The research of

Differential Immune Responses and Protective Effects in Avirulent Mycobacterial Strains Vaccinated BALB/c Mice - Laicheng Liu; Ruiling Fu; Xuefeng Yuan; Chunwei Shi; Shuling Wang; Xianyu Lu; Zhao Ma; Xiaoming Zhang; Weiyan Qin; Xionglin Fan (Current Microbiology, 2015)

Assessment of heavy metal contamination in the sediments from the Yellow River Wetland National Nature Reserve (the Sanmenxia section), China - Qingli Cheng; Ruiling Wang; Wenhai Huang; Wenlin Wang; Xudong Li (Environmental Science and Pollution Research, 2015)

Development and evaluation of a new interferon-gamma release assay for the diagnosis of tuberculosis infection in HIV-infected individuals in China - Liang Yu; Pingzheng Mo; Zeping Wei; Ruiling Fu; Mai Yang; Binying Ji; Jian Wang; Shu Li; Amie J. Strong; Neal Touzjian; Nicholas Kushner; Xi-En Gui; et al. (Infectious Diseases, 2015)

Solution Behavior of PVP-VA and HPMC-AS-Based Amorphous Solid Dispersions and Their Bioavailability Implications - Feng Qian; Jennifer Wang; Ruiling Hartley; Jing Tao; Raja Haddadin; Neil Mathias; Munir Hussain (Pharmaceutical Research, 2012)

Environmental flows and its evaluation of restoration effect based on LEDESS model in Yellow River Delta wetlands - Xingong Wang; Yu Lian; Chong Huang; Xiaojun Wang; Ruiling Wang; Kai Shan; Bas Pedroli; Michiel van Eupen; Amgad ElMahdi; Mahtab Ali (Mitigation and Adaptation Strategies for Global Change, 2012)

A DNA vaccine expressing CFP21 and MPT64 fusion protein enhances BCG-induced protective immunity against Mycobacterium tuberculosis infection in mice - Chun Wang; Zhenhua Chen; Ruiling Fu; Ying Zhang; Lingxia Chen; Li Huang; Jinjin Li; Chunwei Shi; Xionglin Fan (Medical Microbiology and Immunology, 2011)